Arenigian tholeiitic basalts in the famatina ordovician basin, northwestern Argentina: Emplacement conditions and their tectonic significance - Cisterna, Clara Eugenia (2017)
This study is focused on the analysis of volcanic deposits that crop out at the middle portion of the Las Planchadas range, northern part of the Famatina System in Argentina. These volcanic rocks are records of an Ordovician effusive basaltic volcanism that took place under subaqueous marine conditions. Along the study area crop out an Arenigian volcanic and volcaniclastic rocks succession with massive and autoclastic lavas, hyaloclastites of basaltic composition and volcaniclastic sandstones and mudstones. Large volumes of the volcanic deposits were strongly affected by fragmentation processes during their subaqueous emplacement and in situ accumulated as basaltic breccias. The same volcanic-volcaniclastic association crops out to the south of the Las Planchadas range, forming a basaltic belt with similar characteristics. The geochemical features of the basalts are compatible with depleted mid-ocean ridge basalt (MORB)-like source for the magma, with contribution of subducted related components such as water rich marine hemipelagic sediments, compatible with a back arc geotectonic setting developed along the northern part of the Famatina System during the Arenigian.